ASSESSING VOCABULARY IN THE LANGUAGE CLASSROOM - Fitri Rayani Siregar (State Institute for Islamic Studies IAIN of Metro, 2015)
Vocabulary is ultimate aspect in learning a language. A student who learns a foreign language should have a lot of vocabularies to developt some skills, namely speaking, writing, reading and listening. Also, the teacher needs a guide in assesing the tasks, examinition, and daily tasks.